Innovation of Using Hybrid Modules in Muhammadiyah Elementary School in Sleman as Alternative Distance Learning Solutions in the Covid-19 Pandemic - Abdullah Mukti; Agus Suroyo; Hasanudin (Universitas Ahmad Dahlan, 2022)
The pandemic has turned the education and learning process into distance learning and learning from home. These changes do not necessarily run smoothly. However, there are many obstacles and problems. These include internet network access, the absence of quotas and the process of changing without being conditioned before. Not to mention the complaints from parents who usually leave it entirely to the school, but with the pandemic, parents seem to be